Proceedings of the Twelfth Conference on Applied Linguistics (CONAPLIN 2019) 2020
DOI: 10.2991/assehr.k.200406.020
|View full text |Cite
|
Sign up to set email alerts
|

Deixis Investigation of Motivational Speech in Jack Ma’s “Empowering Young African Entrepreneur in Nairobi” Speech

Abstract: This study aims to investigate the types of deictic expressions used by Jack Ma in one of his speeches in Nairobi and how these deictic expressions helped him in motivating his audience. Drawing on Fillmore's (1997) category of deixis, this qualitative study found that three types of deixis were present in Jack Ma's speech with the person deixis as the most frequently used type. Furthermore, the use of these deictic expressions constructs the deictic field where Jack Ma situated himself at the deictic centre. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The person deixis is the dominant one in the articles of Jakarta Post. This finding is supported by previous studies who found that person deixis is always found in written text or spoken one (Nasution, Setiadi, Ilza, 2018;Wibowo & Nailufar, 2019;Rahayu & Kurniawan, 2019;Laia, 2020)…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The person deixis is the dominant one in the articles of Jakarta Post. This finding is supported by previous studies who found that person deixis is always found in written text or spoken one (Nasution, Setiadi, Ilza, 2018;Wibowo & Nailufar, 2019;Rahayu & Kurniawan, 2019;Laia, 2020)…”
Section: Discussionsupporting
confidence: 86%
“…Many researchers had analysed the types of deixis in novel, poetry, song lyrics, newspaper, teachers' talk, students' talk, drama and speech from 2014 until 2020. Their results were almost the same, where Some researchers found about person, place, time deixis (Quinto, 2014;Sari, 2015;Nugarah, 2015;Purba, 2015;Hasanah, 2016;Asy'ari, Rita, Usman, 2017;Putri & Budiarsa, 2018;Wibowo & Nailufar, 2019;Rahayu & Kurniawan, 2019;Laia, 2020), while several found other types of deixis, such as discourse and social deixis (Wahyudi, 2014;Widayanti & Yuwono, 2017;Retnowati, Nasution, Setiadi, Ilza, 2018).…”
mentioning
confidence: 75%
“…It could be the singers' way of conveying the message (Quinto, 2014). Rahayu & Kurniawan (2020) add that the changes in time periods reference can be used to show the audience related to past experiences or the things that can be done in the future. So it can be concluded that temporal deixis is used to refer the time when the lyrics happen.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Deictic is a key link between time, space, and related subjects (Stapleton, 2017). Deixis is also part of pragmatic that focuses on contextual meaning (Rahayu & Kurniawan, 2020). Yule (in Stapleton, 2017) says that deixis comes from the classical Greek "deiknynai", which means "to point".…”
Section: Progress In the International Readingmentioning
confidence: 99%
“…Spatial or place deixis is a word pointing a direction of the utterance such as; the adverbs here and there, and the demonstrative pronouns this and that. Temporal deixis or time deixis involves a specific time (Fillmore in Rahayu & Kurniawan, 2020). The deictic time adverbs in English language are like now, today, yesterday.…”
Section: Progress In the International Readingmentioning
confidence: 99%